PHENOMENON OF DEMIKHOV. "Experimental Transplantation of Vital Organs" (1960). Myocardial revascularization, experimental physiology of blood circulation - S. P. Glyantsev (Трансплантология (Москва), 2018)
The article (the last of five) presents the analysis of the final (6th and 7th) chapters from V.P. Demikhov's monograph "Experimental Transplantation of Vital Organs" (Medgiz State Press for Medical Literature in Moscow, 1960), where he described the experimental development of the mammarocoronary bypass(anastomosis) surgiclal techniqiue and the experiments to study the physiology of blood circulation.